STERNOCLEIDOMASTOID REGION RESTORATION WITH LATERAL HEMISOLEUS MUSCLE INCORPORATIED IN FREE FIBULAR FLAP FOR RECONSTRUCTION OF RADICAL NECK DISSECTION AND HEMIMANDIBULECTOMY - BAYRAMİÇLİ, MEHMET NURİ ÜMİT (WILEY-BLACKWELL, 2011)
In the treatment of head and neck carcinoma, radical cervical lymphadenectomy leaves the affected side of the neck devoid of the sternocleidomastoid muscle, thus more vulnerable to the unwanted side effects of the adjuvant radiotherapy. It also causes asymmetry and cosmetically unpleasant appearance of the cervical region. In the reported case with widely ulcerated squamous-cell carcinoma over mandible, hemimandibulectomy and radical neck dissection was performed. Following the mandibular reconstruction, the lateral hemisoleus muscle of the harvested osteomyocutaneous fibula flap was utilized to restore the ipsilateral sternocleidomastoid region. This new application promises to be a useful method, which can aid in the restoration of the aesthetic contour of the neck and provide protection against unwanted effects of the adjuvant radiotherapy on the ipsilateral carotid artery. (C) 2011 Wiley-Liss, Inc. Microsurgery 31:401-403, 2011.
Keywords: DEFECTS; COMPOSITE